The phenylselenyl radical and its reaction with molecular oxygen. Issue 40 (3rd October 2017) - Mardyukov, Artur; Tsegaw, Yetsedaw A.; Sander, Wolfram; Schreiner, Peter R.
Abstract : The phenylselenyl radical and its primary oxidation products phenylselenyl peroxy and phenylselenoyl radicals were generated and subsequently isolated in solid noble gas matrices for the first time. Abstract : The current study focuses on the generation, identification, and characterization of the phenylselenyl radical using the matrix isolation technique in combination with density functional theory (B3LYP/cc-pVTZ) computations. The hitherto unknown phenylselenyl peroxy radical was synthesized by co-condensation of the phenylselenyl radical with molecular ground state triplet oxygen from the gas phase and subsequent trapping in argon matrices at 10 K. The experimental IR spectra including 18 O isotopically labelled materials compare well with the data obtained from B3LYP/cc-pVTZ computations. Upon 312 nm irradiation, the phenylselenyl peroxy radical isomerizes to the thermodynamically more stable equally novel phenylselenoyl radical.